Search for lepton-flavour-violating H → μτ decays of the Higgs boson with the ATLAS detector - Aad, G. (2015)
A direct search for lepton–flavour–violating (LFV) H → µτ decays of the recently discovered Higgs boson with the ATLAS detector at the LHC is presented. The analysis is performed in the H → µτhad channel, where τhad is a hadronically decaying τ–lepton. The search is based on the data sample of proton–proton collisions collected by the ATLAS experiment corresponding to an integrated luminosity of 20.3 fb−1 at a centre–of–mass energy of √ s = 8 TeV. No statistically significant excess of data over the predicted background is observed. The observed (expected) 95% confidence–level upper limit on the branching fraction, Br(H → µτ), is 1.85% (1.24%).